Perancangan System Pompa Air Tenaga Surya Terhadap Produktivitas Pertanian Padi (Sawah) - Akmal Muhammad Atthoriq; Jojo Sumarjo; Ratna Dewi Anjani (Peneliti.net, 2022)
The purpose of this research is to design the system and to find out how efficient this solar water pump system is for the productivity of rice/rice fields. The research method begins with analyzing the system design of the solar water pump so that it can be adapted and applied to the solar water pump system. Then the test is carried out by taking data from the incoming power and outgoing power so that the efficiency of this solar water pump can be calculated. And don't forget to analyze from an economic point of view the advantages of using a solar water pump. The results of the research on the design of a solar water pump on the productivity of rice/paddy farming are for rice fields with a size of 1 hectare, the available NPSHa value (9.424072 m) > NPSHr required (0.0309654 m) is chosen so that a water pump with specifications of 40 x 32 B4 – 50 ,4. And for the test results of the solar water pump, the lowest input power is at 6.00 at 10.3 Watt with a light intensity of 15800 Lux, and the highest input power is at 11.00 at 64.5 Watt with a light intensity of 97000 Lux. As for the output power, the average mechanical output power of the pump is 3.49 Watt and the electric power of the pump is 153.8 Watt. And the average efficiency value for mechanical output power is 13.04%. This means that the solar water pump that the researchers tested can work well but requires a larger input power to be even more efficient, this solar water pump is also more cost-effective because it uses free energy sources for its application.